Development of fertilizer automation in IoT-based agriculture monitoring framework using node-red - See, Keng Lek (2024)
Amidst the backdrop of a rapidly expanding global population and mounting concerns surrounding food security, it becomes imperative to revolutionize traditional farming practices while maintaining environmental sustainability. This study employs cutting-edge technology, notably the Internet of Things (IoT), to devise an innovative solution tailored for indoor crop cultivation, focusing on water-intensive crops such as strawberries and cabbages. This specialized system meticulously monitors critical variables such as water quality, ensuring optimal conditions for plant growth, while also automating nutrient delivery processes. Additionally, the system incorporates water recycling mechanisms, thus promoting eco-conscious farming practices. Farmers stand to benefit significantly from this advanced framework, as it enables increased crop yield, resource conservation, and environmental stewardship. By disseminating our findings, we aspire to catalyze widespread adoption of smart agricultural technologies, fostering a more sustainable and environmentally friendly approach to farming worldwide.